The Role of Strategic Management of The Goethe-Institute Bandung Library in Increasing Competitiveness Through Workshop Activities - Zahra, Diyanah Salsabila; Rachmawati, Tine Silvana; Perdana, Fitri (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
Strategic management involves the formulation, implementation, and evaluation processes that play a crucial role in enhancing competitiveness and achieving organizational goals. Through strategic management, the Goethe-Institute Bandung Library as a specialized library can conduct workshops that are competitive in its environment. The method used is descriptive qualitative. The sample in this study consists of 5 informants, including 2 librarians from the Goethe-Institute Bandung Library and 3 users of the library. Data collection techniques include interviews, observations, documentation, and literature review. The data analysis technique uses the Miles and Huberman model, which involves data reduction, data presentation, and conclusion drawing. The result of this study indicate that the strategic management implemented by the Goethe-Institute Bandung Library plays an important role in enhancing competitiveness through the workshops organized. The strategic management applied includes the process of environmental scanning to understand the strengths and weaknesses in the internal and external environment, the strategy formulation process to set long-term goals, the strategic implementation process through the organization workshop activities, and the strategy evaluation process to measure performance and outcomes..